2005
DOI: 10.1007/s00726-005-0231-8
|View full text |Cite
|
Sign up to set email alerts
|

The peptide molecular links between the central nervous and the immune systems

Abstract: The central nervous system (CNS) and the immune system were for many years considered as two autonomous systems. Now, the reciprocal connections between them are generally recognized and very well documented. The links are realized mainly by various immuno- and neuropeptides. In the review the influence of the following immunopeptides on CNS is presented: tuftsin, thymulin, thymopoietin and thymopentin, thymosins, and thymic humoral factor. On the other side, the activity in the immune system of such neuropept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 189 publications
1
10
0
Order By: Relevance
“…These results suggested that thymulin could exert positive feedback regulation on the secretion of GnRH in the hypothalamus of rats actively immunized with GnRH. This is consistent with the hypothesis that thymulin may be part of a feedback loop acting on neuroendocrine organs, such as the hypothalamus, and modulates the stimulatory activity of GnRH on LH and FSH release from pituitary cells (Hinojosa et al 2004, Siemion et al 2005. In addition, thymulin plays a neuroprotective role in different areas of the brain that interact with a set of cytokines (Safieh-Garabedian et al 2011).…”
Section: Figuresupporting
confidence: 89%
“…These results suggested that thymulin could exert positive feedback regulation on the secretion of GnRH in the hypothalamus of rats actively immunized with GnRH. This is consistent with the hypothesis that thymulin may be part of a feedback loop acting on neuroendocrine organs, such as the hypothalamus, and modulates the stimulatory activity of GnRH on LH and FSH release from pituitary cells (Hinojosa et al 2004, Siemion et al 2005. In addition, thymulin plays a neuroprotective role in different areas of the brain that interact with a set of cytokines (Safieh-Garabedian et al 2011).…”
Section: Figuresupporting
confidence: 89%
“…Over the last 20 years, a number of investigators have demonstrated interactions between the immune and neural systems during normal organismal development (Patterson, 1994;Armstrong et al, 2003;Siemion et al, 2005;Wrona, 2006). Our laboratories have been investigating proteins that regulate innervation during the earliest stages of inner ear development (reviewed by Barald and Kelley, 2004;Gerlach et al, 2000), and our recent work highlights the importance of chemokines and cytokines in the early stage peripheral auditory system (Bianchi et al, 2005;Holmes et al, 2011;Shen et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…T␣1 possesses the ability of influencing the central nervous system [68,70]. Its modulatory effect on the excitatory synaptic transmission in cultured hippocampal neurons was documented [81].…”
Section: Other Functionsmentioning
confidence: 99%